348 SEQUENTIAL PEER AND SELF-ASSESSMENT OF ROLE PLAYS AS A TOOL TO BRIDGE THE GAP BETWEEN LEARNING AND PRACTICE. (10th December 2015) - Talente, G. M.; Ho, G.; Kraemer, M. S.
Abstract : Purpose: Teaching competencies such as empathy and communication skills is difficult. Our institution has instituted a curriculum to teach these competencies in an interactive workshop setting. The challenge is connecting what the resident learns with their clinical practice. We set out to design and evaluate an educational model using sequential peer and self-assessment to bridge the gap between learning and practice. Methods: Three case scenarios were designed to test communication skills and the ability to provide empathic, patient-centered care. All second year residents participated. Residents were divided into groups of three and role-played the scenarios. This session was videotaped. After this session they completed peer and self-assessment surveys. The surveys consisted of 20 items measuring their confidence, overall performance, and use of specific behaviors related to the competencies being taught. The residents then received interactive workshops on empathy, communication skills, and other related topics. They then viewed their role-play session and were asked again to complete peer and self-assessments. At a final wrap-up session they were given feedback. Evaluation of the teaching model was based on comparing the change in ratings between the two assessments and surveying of the participants' impression of the training model. Residents rated the experience on a 10-point scale (eg. 1 = not useful, 10 = very useful) and in open-ended responses. Results: 20 residents participated. The residents rated themselves and their peers highly on both the initial and final assessment of the role-play session. The differences between ratings on all items between the two sessions were small and not statistically significant. They rated the overall experience as useful (mean 8.79, range 7-10). They agreed that the role-play and sequential assessments provided a connection between what they learned and clinical practice (mean 8.33, range 5-10). They stated they learned something new from the sequential assessments (mean 8.53, range 6-10) and that the educational sessions changed their peer and self-assessments (mean 8.29, range 5-10). Comments regarding the sequential assessments were positive. One resident stated, "As far as affecting how I practice it was the most useful thing." Conclusions: Objectively measuring the impact of this training model on peer and self-assessment was not successful with the survey used and will require the use of different tools in future iterations. Initial subjective data suggest that this model may provide a way to bridge the gap between learning and practice when teaching the competencies of empathy and communication skills.